Toxoplasma gondii Antibodies in Raw Milk and Sera of Cows in China - Yu-Min Liu; Yang-Yang Zhang; Lu Wang; Hai-Yang Wang; Chun-Hua Li; Yu-Hang Jiang; Wu-Wen Sun (Pathogens, 2022)
Toxoplasma gondii is a worldwide food-borne protozoa that has harmful influences on animal and human health. Raw milk containing T. gondii has been considered as one of the possible infectious sources for humans. Although China is one of the world’s leading milk consumers, there is still no study to investigate the seroprevalence of T. gondii in raw cow milk in China; especially for cows in rural areas. Thus, we conducted this study to examine the specific anti-T. gondii IgG-antibody in the raw milk and sera of domestic cows in China. In total, 894 cows were randomly selected from rural areas in northeastern China. The positive rate of T. gondii in the milk and serum samples were 6.38% (57/894) and 7.16% (64/894), respectively. Moreover, a history of abortion (OR = 2.03, 95% CI: 1.11–3.72, p = 0.022) was identified as the only risk factor for T. gondii infection in the studied cows. This study investigated the seroprevalence of T. gondii in the raw milk and sera of cows in China; it provided timely and useful data for public health and food safety, especially in rural areas.